Comparative analysis for quantification of heart rate viability (HRV) - Wan Mahani Hafizah Wan Mahmud, 1987-, author; Malarvili Balakrishnan; Fakulti Biosains dan Kejuruteraan Perubatan (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2009)
Project Paper (Sarjana Muda Sains (Bio-Perubatan)) - Universiti Teknologi Malaysia, 2009